Time - Snedden, Robert (Belitha Press, London, 1994)
Looks in detail at the scientific quest for greater understanding of time and its complex role in the universe. Topics include how time has been measured throughout history, absolute time, relative time, and time and space. Suggested level: intermediate, secondary